Left, Right and Beyond: the Pragmatics of Political Mapping - Jonathan White (London School of Economics and Political Science (LSE), European Institute, 2010)
This paper examines the political categories of 'Left' and 'Right', in particular as they are evoked and instrumentalised by political actors in the democratic process. Drawing on some of the insights of positioning theory, it shows how 'Left' and 'Right' are discursive resources deployed, contested and resisted in political exchange. The paper looks in depth at some of the political uses to which Left-Right talk may be put, discussing in particular acts of partisan profiling, of legitimisation and subversion, and the evocation or rejection of political continuity. The paper argues that while these usages can be seen as strategic moves pursued for political advantage, they have a larger significance insofar as they indicate one of the ways the democratically important imagery of Left and Right may remain active in European politics.
Keywords: 330